ANTI SHIΓÇÖISM IN INDONESIA: GENEALOGY, DEVELOPMENT, AND METHODS (Harmoni, 2017)
The notion of anti ShiΓÇÖsm is founded in many countries such as Saudi Arabia, Pakistan, Iraq, Syria, and some others countries in South East Asia: Indonesia, Malaysia and Brunei Darussalam. This paper discusses the origin, development, and methods of anti ShiΓÇÖism in Indonesian context. In order to understand the anti ShiΓÇÖism this also will cover the responses expressed by majority Sunni in general and in particular some religious group that continually show their anti Shia sentiment in vary of methods, including the anti ShiΓÇÖism in social media and the establishment of National of Anti Shia Alliance, known as ANAS (Aliansi Nasional Anti Shia).
Keywords: anti-ShiΓÇÖism; heresy, minority; majority; prejudice; Anti Syiah; bidΓÇÖah; Minoritas; Mayoritas; Prasangka